Crypto Crowds : Singularities and Multiplicities on the Blockchain - Matan Shapiro (Berghahn Books, 2024)
Ownership of cryptocurrencies features contrasting forms of mobilization. On one hand, it denotes association with a global crowd of unrelated individual investors, which expands as it attracts more members. On the other hand, it includes participation in grassroots communities, which are generally more insular. Crypto Crowds demonstrates how this tension generates political, economic and moral realities in different cultural and geographical contexts. Pioneering in its approach to cryptocurrency trading, this volume will inspire scholars interested in the sociality of decentralized business models, boom-and-bust cycles on the blockchain, libertarian utopias and other postmodern crowding phenomena.